Neodeightonia guineensis sp. nov., a palmicolus species from Guangdong, China - Xiong, Yinru; Manawasinghe, Ishara S.; Lu, Li; Mapook, Ausana; Alotibi, Fatimah; Hyde, Kevin D. (Phytotaxa, 2025)
Palm fungi encompass nearly all major fungal taxa and possess a broad spectrum of ecological roles. Neodeightonia species are mainly associated with a wide range of palm trees. In this study, a saprobic Neodeightonia species was isolated from Elaeis guineensis in Xishuangbanna, Yunnan Province, China. For species delineation, morphological characteristics and phylogenetic analysis of the internal transcribed spacer (ITS), and translation elongation factor 1−alpha gene (tef 1-α) were conducted. Based on the phylogenetic results and morphology, Neodeightonia guineensis is introduced as a new species along with a description and illustrations. Additionally, the taxonomic status of some species within Neodeightonia is discussed. Based on our phylogenetic and morphological comparisons, ITS and tef 1-α gene region play the most important role in species delineation in Neodeightonia species. This is the first report of a Neodeightonia species associated with Elaeis guineensis, thereby enhancing the diversity of fungi associated with palm trees.